(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
Cultured meat remains in the early stages of development and has yet to achieve widespread commercial adoption, particularly in Muslim-majority regions. While ongoing research and technological advancements aim to bring cultured meat to market, its acceptance among Muslim communities is still limited due to religious and ethical concerns. Understanding the religious and cultural perspectives that shape attitudes toward novel food technologies is essential for addressing potential challenges and ensuring ethical integration into Islamic dietary practices. This study aims to critically examine the ethical, religious, and societal implications of cultured meat from an Islamic perspective, with a particular focus on its halal status through the lens of Qawāʿid Fiqhiyyah (Islamic legal maxims). By analyzing existing literature and scholarly discussions, this research provides valuable insights for policymakers, religious scholars, and the scientific community in navigating the permissibility and ethical considerations of cultured meat within Islamic dietary laws. A qualitative case study approach is employed, utilizing secondary data from relevant studies and scholarly works. The findings contribute to the broader discourse on sustainable food production while addressing the religious concerns of Muslim consumers.